Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/6319685
|View full text |Cite
|
Sign up to set email alerts
|

hnRNPC Promotes Malignancy in Pancreatic Cancer through Stabilization of IQGAP3

Abstract: Due to challenges in early-stage detection, aggressive behavior, and poor response to systemic therapy, pancreatic cancer is one of the most fatal cancer types globally. The role of RNA-binding protein (RBP) transcription and translation of cancer cells has been well demonstrated, although their roles in pancreatic cancer is less well understood. In this study, we found that heterogeneous nuclear ribonucleoprotein C (hnRNPC), a RBP, is highly expressed in pancreatic ductal adenocarcinoma (PDAC) tissues and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…IQGAP3 expression was not found in the nonneoplastic pancreatic ductal epithelium but in the cytoplasm and cell membranes of cancer cells, suggesting that its expression is relatively specific to cancer. Although elevated expression of IQGAP3 has been previously confirmed in PDAC at the mRNA level [21,32], this report is the first to confirm IQGAP3 protein expression in PDAC using IHC. Moreover, IQGAP3 expression was an independent poor prognostic factor in our immunostaining-based analysis and analyses of the TCGA PAAD dataset.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…IQGAP3 expression was not found in the nonneoplastic pancreatic ductal epithelium but in the cytoplasm and cell membranes of cancer cells, suggesting that its expression is relatively specific to cancer. Although elevated expression of IQGAP3 has been previously confirmed in PDAC at the mRNA level [21,32], this report is the first to confirm IQGAP3 protein expression in PDAC using IHC. Moreover, IQGAP3 expression was an independent poor prognostic factor in our immunostaining-based analysis and analyses of the TCGA PAAD dataset.…”
Section: Discussionmentioning
confidence: 66%
“…It is reported that in the mouse stomach corpus, the IQ-GAP3-ERK-CD44 axis drives stem cell proliferation during homeostasis and tissue repair [38]. A previous study has shown that IQGAP3 acts as an oncogene by regulating Cdc42 expression [21], and heterogeneous nuclear ribonucleoprotein C promotes PDAC progression via IQGAP3 stabilization [32]. It would be desirable to place IQGAP3 in the context of tumor progression by examining the genes associated with IQGAP3, which can be an essential basis for increasing the potential of IQ-GAP3 as a precision therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, HNRNPC could promote proliferation and metastasis and inhibit prognosis [ 31 ]. Additionally, upregulation of HNRNPC in metastatic in vivo models could accelerate tumorigenesis in PC [ 32 ]. Moreover, bioinformatics analysis and immunohistochemical staining revealed that HNRNPC was negatively associated with the OS in LUAD [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TMEM150A expression levels were correlated with immune cell markers such as STAT5A, ITGAM, CCL2, TGFB1, IRF5, FOXP3, CD68, CSF1R, STAT6, HLA-DPB1, GATA3, HLA-DPA1, CD163, STAT3, CD86, IL10, HLA-DRA, CD3-E, ITGAX, MS4A4A, KIR2DL4, HAVCR2, CD2, CD3-D, CTLA4, and others. Additionally, RNA modification genes, such as RBMX, HNRNPC, ALKBH5, and WTAP, play a crucial role in cancer biology [32][33][34][35][36][37][38]. For instance, the inhibition of ALKBH5 expression in GSCs significantly down-regulated stem cell survival and invasion after irradiation and mediated the radioresistant properties of stem cells [33].…”
Section: Plos Onementioning
confidence: 99%